TYPOLOGY OF FOLKLORISMS IN THE POETRY OF IQBOL MIRZO (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the poetic functions of folklore in Iqbol Matzo’s poetry, the analysis of the poet's skill in using simple and complex (analytical, stylistic, synthesized, ethnographic) folklorisms. In particular, the article "Muhammad Yusuf" (“Muhammad Yusuf”), "Ramadan" (“Ramazon”), "Snowdrop" (“Boychechak”), "Question" (“So’roq”), "My dad" (“Dadam”), "Gold ring" (“Tilla uzuk”, "I gave to God" (“Xudoga soldim”), "Story about fairy" (“Pari haqida hikoya”), "My dad's grave" (“Dadam qabri”), "Navruzguli”(meaning: flower named after Navruz) (“Navro’zguli”), "Song of Navruz" (“Navro’z qo’shig’i”) are analyzed and folklorisms serves to express the poet's ideological goal.